Impacts of translocation on a large urban-adapted venomous snake - Wolfe, Ashleigh; Fleming, P.; Bateman, Bill (C S I R O Publishing, 2018)
Context Translocation as a tool for management of nuisance or 'problem' snakes near urban areas is currently used worldwide with limited success. Translocated snakes experience modified behaviours, spatial use and survivorship, and few studies have investigated the impacts of translocation within a metropolitan area. Aims In the present study, we investigated the impacts of translocation on the most commonly encountered snake in Perth Western Australia, the dugite (Pseudonaja affinis, Elapidae), by comparing the space use of resident and translocated snakes. Methods We captured 10 dugites and attached telemetry packages, composed of a radio-telemetry transmitter and global positioning system (GPS) data-logger, externally to their tails. Snakes were either released within 200 m of their initial capture sites (residents, n = 6) or moved to new unconnected habitat at least 3 km away (translocated, n = 4). Spatial-use data were analysed using general linear models to identify differences between resident and translocated dugites. Key results Translocation influenced space use of dugites and detrimentally affected their survivorship. Translocated snakes had larger activity ranges than did residents, and there was a trend towards travelling greater distances over time. Mortality for all snakes was high: 100% for translocated snakes, and 50% for residents. Conclusions Urban dugites face many threats, and snakes were negatively affected by translocation. The GPS technology we used did not improve the quality of the data over traditional radio-telemetry methods, owing to the cryptic nature of the snakes that spent much of their time under cover or underground. Implications These findings support the growing body of evidence that translocating 'problem' snakes is a not a humane method of animal management, and alternatives such as public education, may be more appropriate.